IMPLEMENTASI PEMBELAJARAN MANDIRI DALAM PROGRAM PENDIDIKAN KESETARAAN: STUDI KASUS DI PKBM SONGGO LANGIT - Gita Pareira; Defa Yusmita; Yessi Wahyuningsih; Fitria Islami; Zaky Aldika; Asti Ajeng Natasyah (Universitas Negeri Medan, 2026)
Limited learning time for residents to study the Equality Education Program at PKBM Songgo Langit Bengkulu City because the majority of workers encourage the implementation of self directed learningas a solution to balance work and education. This study aims to describe the application of self directed learningwhich includes planning, implementation, and evaluation. The research uses a descriptive qualitative method with observation, interview, and documentation techniques. The data was analyzed through reduction, presentation, and conclusion drawing and tested for validity by triangulation. The results of the study show that planning is carried out through goal setting, material selection, and preparation of independent modules according to the needs of learning residents. The implementation takes place flexibly through module-based assignments, tutor assistance with an andragogy approach, and communication using digital media. Evaluation is carried out on an ongoing basis through monitoring the learning process, assignment assessment, and post-test at the end of each semester. Self directed learninghas been proven to increase the flexibility, independence, and learning outcomes of learning residents. This study concludes that the self directed learningmethod is effectively applied to the Package C Equality Program because it is able to overcome time constraints and encourage students' learning responsibilities.